Prevalence trends of anemia impairment in adolescents and young adults with HIV/AIDS - Xinqi Li; Nan Zhang; Linlu Ma; Qian Wang; Yuxing Liang; Xiaoyan Liu; Fuling Zhou (BMC, 2024)
Abstract Background Anemia is a common complication of HIV/AIDS, particularly in adolescents and young adults across various countries and regions. However, little is known about the changing prevalence trends of anemia impairment in this population over time. Methods Data on anemia in adolescents and young adults with HIV/AIDS from 1990 to 2019 were collected from the Global Burden of Disease. Prevalence was calculated by gender, region, and country for individuals aged 10-24, and trends were measured using estimating annual percentage changes (EAPC). Results Globally, the prevalence of adolescents and young adults with HIV/AIDS increased from 103.95 per 100,000 population in 1990 to 203.78 in 2019. However, anemia impairment has decreased over the past three decades, with a global percentage decreasing from 70.6% in 1990 to 34.7% in 2019, mainly presenting as mild to moderate anemia and significantly higher in females than males. The largest decreases were observed in Central Sub-Saharan Africa, North America, and Eastern Sub-Saharan Africa, with EAPCs of -2.8, -2.34, and -2.17, respectively. Tajikistan (78.76%) and Madagascar (74.65%) had the highest anemia impairment percentage in 2019, while China (16.61%) and Iceland (13.73%) had the lowest. Anemia impairment was closely related to sociodemographic index (SDI) levels, with a high proportion of impairment in low SDI regions but a stable decreasing trend (EAPC = -0.37). Conclusion Continued anemia monitoring and management are crucial for patients with HIV, especially in high-prevalence regions and among females. Public health policies and interventions can improve the quality of life and reduce morbidity and mortality.